Charlemagne – Emperor and Reformer. On the 1200th Death Anniversary - Ratajczak, Krzysztof (Biuletyn Historii Wychowania, 2018)
The purpose of this paper is to present the role of Charlemagne (768−814), King of the Franks and Emperor of the Romans (from 800) in the process of recovering the school organisation that was considerably weakened in the period from the 5th to the 7th century as well as the participation of the ruler in the reforms of education, science and the school system, referred to as the Carolingian Renaissance. In his reforms of the legal system, the monetary system, administration and education, Charles consistently implemented the political program announced in the Act of 789. The emperor’s actions reveal a clearly utilitarian goal. The command of Latin and the introduction of readable writing enabled the clergy to better understand the words of the Holy Scripture and, in turn, increased the general level of religious education among believers. The numerous scriptoria across the empire contributed to the ongoing work on defining the uniform text of all the books. The rebirth of Latin was driven by the works of the late Roman grammarians, Donatus and Priscian, and many works by ancient authors were also copied in scriptoria.